The Relationship between Knowledge and the Application of Ethical Principles of Anesthesia Principals - Ni Nyoman Ari Kundari Dewi; Agus Baratha Suyasa; Ni Luh Putu Lusiana Devi; Luh Gde Nita Sri Wahyuningsih (GLOBAL HEALTH SCIENCE GROUP, 2024)
Anesthesia technicians in providing health services should be guided by the code of ethics of anesthesia technicians. This can certainly have a positive impact on health services and patients of course. This study aims to determine the relationship between knowledge and ethical principles of anesthesia. The anesthesia team is said to have a high risk of committing deviations in providing services.The impact that can arise if anesthesiologists do not apply ethical principlesnamely patient satisfaction can be reduced towards the services provided, due to the suboptimal performance of anesthesiologists. The purpose of this study was to determine the relationship between knowledge and the application of ethical principles of anesthesiologists in Bali. This study used a correlational analytical approach with a cross-sectional approach. The sample in this study was 141 respondents taken using probability sampling techniques with simple random sampling types. Data were collected using questionnaires and analyzed using statistical inference. The questionnaire used was a standard questionnaire with a reliability value of 0.6. The results showed that there was a relationship between knowledge and the application of ethical principles of anesthesiologists in respondents, which found a p-value of <0.001.